A mentally retarded child in the family: Psychological problems of establishing a diagnosis - Pūras, P.; Slavėnaitė, V. (Psichologija, 1990)
The paper reports the results of interviews with parents of 221 severely mentally retarded children. The main attention is paid to the parental reactions to receiving the information about a child's handicap. It has been revealed that children psychiatrists and pediatricians preferred to postpone giving an adequate diagnosis to the parents. On the other hand, retrospective analysis showed that parents valued an early acknowledgment of the problem. Causes and consequences of these psychological phenomena are presented in the paper.
Keywords: mental retardation; family; diagnosis